Efectividad de un módulo de resolución de problemas matemáticos en estudiantes de secundaria del Callao - Fabián, Gloria (2013)
This work describes and evaluates the application of a module to increase the specific abilities set in action when students resolve math problems. Such abilities are: analyzing the problem, identifying and laying out strategies, applying algorithms and revising the process that leads to the solution. The module presents problems solved by the teacher (modelling strategies) and uses the work of peers in order to consolidate and evaluate the work. The study uses a quasi experimental design with two pre defined groups, pre and post test. The sample was not probabilistic and was formed by 70 students. A test with 10 math problems was used as the instrument meant for the students to use the four strategies suggested in the module. Results show a difference in favor of the experimental group, which allows us to conclude that the module has an influence in the evaluated abilities.